Resistance of Collard Green Genotypes to Bemisia tabaci Biotype B: Characterization of Antixenosis - Domingos, G. M. [UNESP]; Baldin, E. L.L. [UNESP]; Canassa, V. F. [UNESP]; Silva, I. F. [UNESP]; Lourenção, A. L. (Springer Nature, 2018)
Bemisia tabaci (Genn.) biotype B (Hemiptera: Aleyrodidae) is an important pest of vegetable crops, including collard greens Brassica oleracea var. acephala (Brassicaceae). The use of resistant genotypes is an interesting option to reduce insect populations and can be used as an important tool for integrated pest management (IPM). This study evaluated 32 genotypes of collard greens against the attack of silver leaf whitefly, with the aim to characterize antixenosis. Initially, a multiple-choice trial was conducted using all genotypes, in which the adult attractiveness was assessed on two leaves per genotype at 24 and 48 h after infestation. After 48 h, one leaf of each genotype was randomly selected for the determination of the number of eggs per square centimeter. From the results of the multiple-choice trial, 13 genotypes were selected for a no-choice oviposition test, following the same method of the previous test. Colorimetric analyses were also performed to establish possible correlations between leaf color and insect colonization. Genotypes HS-20, OE, and VA were less attractive, demonstrating antixenosis. Genotypes LG, VE, J, MG, MOP, HS-20, VA, and MT had less oviposition in the multiple-choice test, which indicated expression of antixenosis. In the no-choice test, genotypes VE, P1C, CCB, RI-919, H, and J had less oviposition, which also characterized antixenosis. Therefore, genotypes VE and J showed the highest resistance stability because both had less oviposition in both test modalities. Thus, the resistance to B. tabaci biotype B indicates the genotypes HS-20, OE, VA, VE, and J are promising for use in breeding programs to develop resistance to whitefly.
Keywords: Aleyrodidae; Brassica oleracea var. acephala; colorimetry; host plant selection; whitefly